2007
DOI: 10.1128/jvi.02664-06
|View full text |Cite
|
Sign up to set email alerts
|

Minor Capsid Proteins of Simian Virus 40 Are Dispensable for Nucleocapsid Assembly and Cell Entry but Are Required for Nuclear Entry of the Viral Genome

Abstract: We investigated the roles of simian virus 40 capsid proteins in the viral life cycle by analyzing point mutants in Vp1 and Vp2/3, as well as a deletion mutant lacking the Vp2/3 coding sequence. The Vp1 mutants (V243E and L245E) and the Vp2/3 mutants (F157E-I158E and P164R-G165E-G166R) were previously shown to be defective in Vp1-Vp2/3 interaction and to be noninfectious or poorly infectious, respectively. Here, we show that all these point mutants form stable particles following DNA transfection into cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 62 publications
(98 reference statements)
3
37
1
Order By: Relevance
“…Furthermore, the requirement for host factors, for physiological conditions (temperature, pH and salt concentration) and for ATP and Mg þ þ is consistent with the participation of chaperones in the in vitro system. A number of investigators have recently reported, based on studies with mutant viruses of both polyoma and SV40, that VP2 and VP3 are not required for the assembly process in vivo, but rather for infectivity, egress and for the transport of the viral genome to the nucleus [14,15,37,41]. Consistent with these data the particles produced here are significantly less infective than wild type SV40.…”
Section: Comparison Of the In Vitro Reaction To In Vivo Assemblysupporting
confidence: 79%
“…Furthermore, the requirement for host factors, for physiological conditions (temperature, pH and salt concentration) and for ATP and Mg þ þ is consistent with the participation of chaperones in the in vitro system. A number of investigators have recently reported, based on studies with mutant viruses of both polyoma and SV40, that VP2 and VP3 are not required for the assembly process in vivo, but rather for infectivity, egress and for the transport of the viral genome to the nucleus [14,15,37,41]. Consistent with these data the particles produced here are significantly less infective than wild type SV40.…”
Section: Comparison Of the In Vitro Reaction To In Vivo Assemblysupporting
confidence: 79%
“…The coexpression of Vp1 and LT/ST from the SV40-derived SVVp1 DNA is sufficient for the formation of minichromosomecontaining virion-like particles in TC7 cells (5). However, it is difficult to discern a direct role of LT or ST in Vp1 folding and assembly in this system, because LT is expressed together with ST and is required to activate the Vp1 promoter in SV-Vp1 and to replicate the minichromosome.…”
Section: Resultsmentioning
confidence: 95%
“…The three capsid proteins have separate and distinct functions in the viral life cycle (5-7). Vp2 and Vp3 are required for the transport of the infecting viral DNA to the cell nucleus (5,7). Vp1 is necessary for the packaging of the viral minichromosome and assembly of the capsid and mediates cell attachment and entry (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear entry of SV40 has been thought to either involve the NPC (after escape of the subviral particles from the ER), or through direct penetration of the inner nuclear membrane from the ER (Figure 3). Several lines of evidence provide support for involvement of the NPC: capsid proteins VP2/3 contain NLSs [47,48], microinjection of anti-VP2/3 antibodies into the cytoplasm prevents SV40 infection [47], importin-a/importin-b interact with SV40 DNA in a complex with viral proteins VP1/3 [48], and virus-like particles that contain NLS-deficient VP3 do not transport their DNA into the nucleus [49]. The initial hypothesis was that the exposed VP2/3 on SV40 disassembly intermediates enter the nucleus along with the genome through the NPC.…”
Section: When One Door Is Shut Another Opensmentioning
confidence: 99%